The Historical Presidency: Clinton's Elections: Redividing Government in the 1990s. Issue 2 (13th May 2016) - Nelson, Michael
Abstract : Divided government has become the norm in American national politics. But its pattern redivided beginning in the 1990s from one of Republican presidents and Democratic Congresses to one of Democratic presidents and Republican Congresses. Drawing on oral history interviews with campaign and administration officials from the Clinton administration, this article explains how Bill Clinton forged a winning strategy for Democratic presidential candidates while contributing to the weakening of the Democratic congressional party.